Investigation of the photoluminescence properties of quantum dots using theoretical simulation - Le Doan Duy; Le Xuan Thuy (Institute of Advanced Engineering and Science, 2026)
This study investigates the optical behavior of CdSe quantum dots, a class of semiconductor nanomaterials widely studied for light-emitting, photovoltaic, and bioimaging applications owing to their size-dependent electronic structure. The objective is to clarify the relationship between quantum dot size, size distribution, and emission characteristics through experimental and simulated optical spectra. UV-Vis absorption, photoluminescence, and simulated PL spectra were analyzed for CdSe quantum dots excited at 325 nm. The experimental PL spectrum exhibits a single and narrow emission band assigned to the 1Se → 1Sh transition, which is blue-shifted compared with bulk CdSe, confirming strong quantum confinement in 2-3 nm particles with a very narrow size distribution of less than 1%. A large Stokes shift of 0.93 eV is observed, attributed to confinement effects and surface-related states. Simulated photoluminescence (PL) spectra for 3-6 nm quantum dots show progressive red-shifting and spectral broadening with increasing particle size, while smaller quantum dots display stronger PL intensity due to enhanced confinement and more efficient radiative recombination. Parameter analysis further reveals that size deviation and linewidth broaden emission and reduce intensity without changing the peak wavelength. These findings provide useful guidance for optimizing CdSe quantum dots for QLEDs, bioimaging, and broadband optoelectronic devices.